Sources, reasons, and requirements. - Guindon, Bruno (Philosophical Studies, 2016)
This paper offers two competing accounts of normative requirements, each of which purports to explain why some-but not all-requirements are normative in the sense of being related to normative reasons in some robust way. According to the reasons- sensitive view, normative requirements are those and only those which are sensitive to normative reasons. On this account, normative requirements are second-order statements about what there is conclusive reason to do, in the broad sense of the term. According to the reasons- providing view-which I attribute to John Broome-normative requirements are those and only those which constitute or provide normative reasons. I argue that the reasons-providing view is susceptible to two serious objections. First, the view generates an explanatory gap. Secondly, the view is implausible. I argue that these two objections give us reason to prefer the reasons-sensitive view of normative requirements over the reasons-providing view.